1995
DOI: 10.1002/bip.360350509
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of polyamides containing unnatural amino acids

Abstract: We describe the synthesis of several polyamides that retain the secondary structure of proteins and contain derivatizable side chains. The derivatizable side chain allows for further reaction of the polymer chain (e.g., chain cross-linking or addition of pendant groups). Polymers of alpha-amino acids containing a terminal unsaturated bond on the side chain have been synthesized. Poly-L-pentenyl glycine, poly-L-propargyl glycine, and poly-L-allyl glycine were synthesized chemically via Leuchs' anhydrides and en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 20 publications
2
17
0
Order By: Relevance
“…Former studies have demonstrated that in statistical copolymers of BLG and L/DL-AG, the AG units acted as defects and that the overall secondary structure of the statistical copolymer was driven by that of the BLG units (in the majority), i.e., α-helical; 55 this, despite the fact that P(DLAG) homo-or block co-polymers are known to form β-sheets. 22,59 The driving force of BLG for the α-helical conformation was also demonstrated in other statistical copolymers of similar BLG to co-monomer (e.g., propargylglycine) ratios. 54 For these reasons, we concluded that AG units behave as 'defects', thereby disrupting the formation of a BLG-driven homogeneous α-helical copolymer.…”
Section: Physical Gelationmentioning
confidence: 88%
See 3 more Smart Citations
“…Former studies have demonstrated that in statistical copolymers of BLG and L/DL-AG, the AG units acted as defects and that the overall secondary structure of the statistical copolymer was driven by that of the BLG units (in the majority), i.e., α-helical; 55 this, despite the fact that P(DLAG) homo-or block co-polymers are known to form β-sheets. 22,59 The driving force of BLG for the α-helical conformation was also demonstrated in other statistical copolymers of similar BLG to co-monomer (e.g., propargylglycine) ratios. 54 For these reasons, we concluded that AG units behave as 'defects', thereby disrupting the formation of a BLG-driven homogeneous α-helical copolymer.…”
Section: Physical Gelationmentioning
confidence: 88%
“…None of our statistical copolymers (Table 1) gelled in toluene at room temperature even for concentrations as high as 50 g L −1 (i.e., 5% w/ v). Interestingly, after maintaining the temperature of the solutions at −35°C for only a few minutes, we observed reversible physical gelation for all P(BLG x -co-AG 1−x ) n -toluene systems (10 to 50 g L −1 ), with exception of P(BLG 0.76 -co-DLAG 0.24 ) 59 .…”
Section: Physical Gelationmentioning
confidence: 92%
See 2 more Smart Citations
“…Poly -l -pentenyl glycine, poly -l -propargyl glycine, and poly -l -allyl glycine were synthesized chemically and enzymatically using subtilisin Carlsberg. Whereas higher molecular weights (DP = 40 -160) were achieved with chemical means, the protease -catalyzed polymers have DP = 8 -12 [37] . In a separate work involving the non -natural amino acid allyglycine ( Ag ), subtilisin Carlsberg was used to synthesize the tetrapeptide ester l -Ag -l -Phe -l -Phe -LAg -OEt in several miscible aqueous/organic solvent systems.…”
Section: Introductionmentioning
confidence: 99%